“I feel safe when I listen to Korean music!”: Musical engagement and subjective well-being amongst Korean international students in the UK - Cho, Hyunah (Journal of International Students, 2024)
By addressing the research question, "How do Korean international students engage in music for their own well-being in the UK?", this study aims to understand a group of international students' experiences of their temporary migrant status and the coping mechanisms they employ in the pursuit of subjective well-being in response to these experiences. After semi-structured interviews, the thematic analysis resulted in five themes: (1) music as a tongbanja 동반자 (companion), (2) music as a safe konggan 공간 (space), (3) music for relationships, (4) music for emotion, and (5) musical demands of international students. This lead to discussions of music as: 'being' a companion and safe space, and 'doing' in relationships and moods, including doing K-pop for ‘re-membering’. Therefore, this study adds depth to understandings of how Korean international students in the UK engage with music to address the challenges they face and, thus, enhance their subjective well-being.